Social media marketing campaign #realsupport to develop consumers brand engagement Uniqlo Indonesia - Dianthea, Anastasia Salsa; Fatonah, Siti; Ardhanariswari, Kartika Ayu (Department of Communication Studies, Faculty of Social and Political Sciences Universitas, 2023)
Various brands are increasingly using social media marketing strategies. This activity encourages companies to increase the emotional bond between brands and consumers. Therefore, local and international brands compete with each other to carry out effective and innovative social media marketing strategies. Through this social media marketing strategy, Uniqlo Indonesia presents the #RealSupport campaign movement with Creative House 6616 with the main objective of getting customer brand engagement while at the same time meeting the key performance indicators of the campaign. Some of the objectives of this study are to 1) find out the process of formulating Creative House 6616's social media marketing strategy in building Uniqlo Indonesia's customer brand engagement. 2) knowing the form of customer brand engagement in Uniqlo Indonesia's #RealSupport campaign. This study uses the concept of Breakenridge's Social Media Strategy Wheel, Media Ecology Theory, and the concept of Customer Brand Engagement. The research method uses descriptive qualitative with case studies through observation and in-depth interviews to collect data. This study finds that Creative House 6616 implements social media marketing strategies organically in every process. By utilizing Key Opinion Leaders, Uniqlo can build engagement on the Uniqlo Instagram account. Not only successful in getting engagement with the achievement of intention to buy and use, intention to recommend, electronic word of mouth, and loyalty, the #RealSupport campaign has also become a social movement to support women throughout Indonesia. The campaign's success can also be seen from the use of the #RealSupport hashtag on all AIRism Uniqlo product variants even though the campaign has long been over